SISTEM TANGGAP DARURAT PENANGGULANGAN KEBAKARAN DI RSUD Prof. Dr. MARGONO SOEKARJO TAHUN 2017 - Alivviya Mariti Alik; Yulianto Yulianto (Buletin Keslingmas, 2018)
AbstractEmergency responsive system for fire countermeasure at RSUD Prof. Dr. Margono Soekarjo in2017. Need of an emergency response system in response to fire in the hospital to protect patients,companion patients, human resurces and hospital visitors from the fire and smoke. The researchmethod use in this research is descriptive, that is by describing clearly the implementation ofemergency response of fire prevention in RSUD Prof. Dr. MargonoSoekarjo, which is compared tothe relevantstandards of legislation.In carrying out emergency respose of fire as the effort of fireprevention in RSUD Prof. Dr. MargonoSoekarjo has provided fire fighting procedures, fireprevention facilities, facilities, evacuation facilities, training and socialization of fire prevention forall people in the hospital. The result of analysis of active fire prevention facility in RSUD Prof. Dr.MargonoSoekarjo shows; APAR of 98,38% which is appropriate with Ministerial Decreeno.04/Men/1980, Hydrant of 77,86% which is appropriate with Minister of Public Work DecreeNo:10/KPTS/2000, Detector of 100% which is appropriate with Permenaker No.Per.02/Men/1983,Fire Pump of 88,33% according to PM PU Number:26/PRT/M/2008, Fire Alarm 85,71% accordingto Permenaker No.Per.02/Men/1983. The conclusion of this research is RSUD Prof. Dr.MargonoSoekarjo has implemented emergency response fire management response as animplementation of fire prevention and control policy in hospital. The suggestion that can be give is thesetting of the placement and installation of APARs which is inappropriate should be appropriated tothe standard, completing the incomplete hydrant box equipment, checking and replacing alarms anddetectors that have been installed in hospital, the addition of sprinkler facilities is also necessary in aplace that have great potential for fire.